Workplace Ostracism and Turnover Intentions: A Moderated Mediation Model of Organizational Commitment and Emotional Intelligence in the Hospitality Industry - Dhungana, Madan; Shrestha, Anisha (Nexus: Journal of Interdisciplinary Engineering, Technology and Management, 2026)
Employee turnover remains a significant and costly issue in the hospitality industry. Ostracism at work, a subtle but significant kind of social exclusion, is an essential predictor of intentions to leave. This study investigates the influence of workplace ostracism on turnover intentions in the hospitality sector of Lalitpur, focusing on organizational commitment as a mediating factor and emotional intelligence as a moderating variable. The study employs Quantitative research methodologies with a causal research design. Moreover, a cross-sectional design was employed to collect data from a sample of 262 employees at five government-classified tourist-standard hotels in Lalitpur.Workplace ostracism demonstrated a direct and positive effect on turnover intentions, and organizational commitment partially mediated this relationship, as indicated by the indirect effect, whereas emotional intelligence significantly reduced the impact of ostracism. When employees feel left out at work, they are more likely to think about leaving their jobs. Organizational commitment can help reduce this risk, but emotional intelligence does not seem to make a difference. This shows that companies should focus on building inclusive cultures instead of relying on individual coping skills. Recognizing employees' efforts helps build commitment and transparency and reduces feelings of exclusion. To truly improve workplace dynamics, organizations need to implement systematic changes alongside encouraging emotional intelligence.